Political party strength and electoral violence. (January 2020) - Fjelde, Hanne
Existing research on the causes of electoral violence has focused on structural determinants and election-specific characteristics but has paid less attention to the role of political agents that contest elections. This study addresses this gap by examining the relationship between the organizational strength of political parties and the risk of electoral violence. The study argues that strong political parties enhance the prospect for peaceful electoral dynamics for two reasons. First, having strong party organizations reduce incentives for violent electoral manipulation because these organizations enable more cost-efficient ways to mobilize voters. Second, strong party organizations constrain political actors from deploying electoral violence, both at the leadership and grassroot levels. The relationship between political party strength and electoral violence is studied by combining global data on the overall strength of political parties in the polity with data on violence across all national elections from 1946 to 2010. The statistical analysis accounts for a number of potentially confounding variables related to formal political institutions and election-specific characteristics. The results point to a statistically significant and substantively important association between strong political parties and a reduced risk of violent electoral conflict.